Pecular files od USSR NKVD-MVD as sourse of news time history. - Pocius, Mindaugas (Genocidas ir rezistencija, 1998)
This article presents the documents contained in Stalin’s ‘Special folder’ files, which reflect the post–war situation in Lithuania. The documents relating to Lithuania can be broken down into the following categories: the activities of the repressive structures of the NKVD–MVD of the USSR and the LSSR in suppressing the Lithuanian resistance, and the measures taken against organisations and individuals in exile.
Keywords: Soviet Union; repressive structures; communist party; emigree; armed resistance